Rapid determination of 12 antibiotics and caffeine in sewage and bioreactor effluent by online column-switching liquid chromatography/tandem mass spectrometry - Lima Gomes, Paulo C. F. [UNESP]; Tomita, Inês N.; Santos-Neto, Álvaro J.; Zaiat, Marcelo (Springer Nature, 2015)
This study presents a column-switching solid-phase extraction online-coupled to a liquid chromatography/tandem mass spectrometry (SPE-LC-MS/MS) method for simultaneous analysis of 12 antibiotics (7 sulfonamides and 5 fluoroquinolones) and caffeine detected in the sewage and effluent of a pilot anaerobic reactor used in sewage treatment. After acidification and filtration, the samples were directly injected into a simple and conventional LC system. Backflush and foreflush modes were compared based on the theoretical plates and peak asymmetry observed. The method was tested in terms of detection (MDL) and quantification limit (MQL), linearity, relative recovery, and precision intra- and inter-day in lab-made sewage samples. The method presented suitable figures of merit in terms of detection, varying from 8.00 × 10(-5) to 6.00 × 10(-2) ng (0.800 up to 600 ng L(-1); caffeine) with direct injection volume of only 100 μL and 13 min of total analysis time (sample preparation and chromatographic run). When the method was applied in the analysis of sewage and effluent of the anaerobic reactor (n = 15), six antibiotics and caffeine were detected in concentrations ranging from 0.018 to 1097 μg L(-1). To guarantee a reliable quantification, standard addition was used to overcome the matrix effect.
Keywords: Antibiotics; Column switching; Spe online; Sewage and anaerobic reactor effluent